Employing Smartphone Health Apps in Weight Management for Adolescents: Analysis on Experiences and Perspectives From Pediatric Providers. (October 2022) - Wen, Xin; Nguyen, Linh N.; Kowalski-Dobson, Theresa M.; Mohammed, Layla; Woolford, Susan J.
The rising popularity of smartphone health applications (apps) offers great potential for facilitating pediatric weight management. Pediatric providers can determine health interventions for young patients with excess weight. We surveyed 51 pediatric providers at a Midwest academic medical institution and found that 78% thought currently available resources were not sufficient for pediatric weight management. In all, 76% of respondents reported use of at least one smartphone health app for their personal health. The quality of pediatric providers' experiences with their favorite app was strongly associated with their willingness to recommend the app to their patients ( P < .001), but few of them have made such a recommendation in practice, mainly due to the lack of either personal knowledge about health apps or about evidence-based health apps for pediatric weight management. Moreover, respondents shared ideas about qualities for an effective health app, which shed new light on developing apps specifically for adolescents with excess weight.